Death of a nurse [compact disc, unabridged] - Beaton, M. C. (Beaton, M. C. Hamish Macbeth mysteries., 2016)
On the appointed evening, Hamish waits for Gloria at the restaurant. And waits. Gloria never shows up. Four days later, Gloria's body washes up on the beach near Braikie. Now without a date and without his former policeman Dick Fraser (who left the force to buy a bakery), Hamish must find out who killed the beautiful new resident of Sutherland, and why, before the murderer strikes again. Print run 40,000.